2010
DOI: 10.1080/02646830903487375
|View full text |Cite
|
Sign up to set email alerts
|

Support following miscarriage: what women want

Abstract: Objective: Miscarriage is a frequent pregnancy complication often accompanied by psychological distress. The current study seeks to query women about their desire for support following miscarriage and specific aspects of content, type and timing of support. Method: An experimenter-designed questionnaire was presented to Internet forums dealing with miscarriage or gynecological medical information. Three hundred and five women participated in the study. Results:The majority of women indicated that they would ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 28 publications
(32 reference statements)
2
33
0
2
Order By: Relevance
“…Research in the UK in the mid-1990s repeatedly demonstrated the need for information and attitudes of medical staff negatively affecting the experience of the management of miscarriage [92][93][94]. More recently, Sejourn, Callahan and Chabrol reported on an internet-based survey of over 300 women who had previously miscarried [95]. They found that the majority of women believed they would have benefited from support following their miscarriage.…”
Section: Psychological Management Of Women Following Miscarriagementioning
confidence: 99%
“…Research in the UK in the mid-1990s repeatedly demonstrated the need for information and attitudes of medical staff negatively affecting the experience of the management of miscarriage [92][93][94]. More recently, Sejourn, Callahan and Chabrol reported on an internet-based survey of over 300 women who had previously miscarried [95]. They found that the majority of women believed they would have benefited from support following their miscarriage.…”
Section: Psychological Management Of Women Following Miscarriagementioning
confidence: 99%
“…Sejourne et al (2010a) found that 86% of women felt that the medical appointment they had after their miscarriage was insufficient for dealing with the issues surrounding the miscarriage and that these women indicated that they would appreciate continuing psychological, social, and emotional support after their miscarriage. The women felt that they were not given sufficient information concerning the causes of miscarriage, the process of miscarriage, what was to be expected after a miscarriage, future pregnancies, and the psychological experience of miscarriage (Sejourne et al, 2010a). Cumming et al (2007) suggest that lack of routine follow-up may increase anxiety in women who have miscarried, while Rowlands and Lee (2010a) posit that such women will benefit from follow-up care.…”
Section: Cumming Et Al (2007) Discussed Clinical Implications Of Thimentioning
confidence: 99%
“…Many women identified that their follow-up medical appointment was insufficient to deal with the issues (Sejourne, N., Callahan, S., & Chabrol, H., 2010a) and concerns (Cumming, et al, 2007) that they had following a miscarriage. Enabling, would allow the nurse practitioner to help navigate the woman's passage through this often difficult life transition and the complexities that come with this journey (Swanson, 1991).…”
Section: Enablingmentioning
confidence: 99%
See 2 more Smart Citations